Evidence from a Randomized Trial That Exposure to Supplemental Folic Acid at Recommended Levels during Pregnancy Does Not Lead to Increased Unmetabolized Folic Acid Concentrations in Maternal or Cord Blood. Issue 3 (27th January 2016) - Pentieva, Kristina; Selhub, Jacob; Paul, Ligi; Molloy, Anne M; McNulty, Breige; Ward, Mary; Marshall, Barry; Dornan, James; Reilly, Rosie; Parle-McDermott, Anne; Bradbury, Ian; Ozaki, Mari; et al.
Abstract: Background: Exposure to higher intakes of folic acid (FA) from fortified foods and supplements, although largely considered beneficial, is associated with unmetabolized FA in the circulation, which has raised some health concerns. Objective: The effect of supplemental FA at a dose of 400 μg/d during pregnancy on unmetabolized FA concentrations in maternal plasma and newborn cord blood plasma was investigated. Methods: A new analysis was performed of blood samples from participants in a randomized trial in pregnancy. Women aged 18–35 y, who had taken 400 μg FA/d as recommended in the first trimester, were recruited at the start of trimester 2 and randomly allocated to receive either 400 μg FA/d ( n = 59) or a placebo ( n = 67) throughout the second and third trimesters until delivery. Unmetabolized FA concentrations in maternal and cord blood samples were measured by LC–tandem MS analysis. Results: In response to the intervention from gestational week 14 through delivery, a higher proportion of women in the FA compared with the placebo group had detectable FA (≥0.27 nmol/L) in plasma, but the difference in concentrations was not statistically significant (mean ± SD: 0.44 ± 0.80 compared with 0.13 ± 0.49 nmol/L, P = 0.38). FA treatment throughout pregnancy resulted in higher cord blood plasma total folate (50.6 ± 20.1 compared with 34.5 ± 14.4 nmol/L; P = 0.004) and 5-methyltetrahydrofolate (50.4 ± 20.3 compared with 34.5 ± 14.4 nmol/L; P = 0.005) concentrations, but FA was detected only in 8 of 53 available cord blood samples, and the proportion of samples with detectable FA concentrations was similar in FA-treated and placebo groups. Conclusions: Plasma concentrations of unmetabolized FA arising from supplemental FA at a dose of 400 μg/d, in addition to FA from fortified foods, were low or undetectable in mothers and newborns. The benefits for mothers and offspring of continuing FA supplementation beyond the first trimester of pregnancy can be achieved without posing any risk of increasing unmetabolized circulating FA, even in those already exposed to FA from fortified foods.